Handbook of research on Innovative management using AI in industry 5.0 - Goel, Richa; Garg, Vikas (IGI Global, 2021)
"This book provides a deeper understanding of the relevant aspects of artificial intelligence that impact all industries , discussing applications of AI and how they are designed to increase efficiency by offering various management techniques"